Synthesis of Stable NAD+ Mimics as Inhibitors for the Legionella pneumophila Phosphoribosyl Ubiquitylating Enzyme SdeC. (16th June 2020) - Madern, Jerre M.; Kim, Robbert Q.; Misra, Mohit; Dikic, Ivan; Zhang, Yong; Ovaa, Huib; Codée, Jeroen D. C.; Filippov, Dmitri V.; van der Heden van Noort, Gerbrand J.
Abstract: Stable NAD + analogues carrying single atom substitutions in either the furanose ring or the nicotinamide part have proven their value as inhibitors for NAD + ‐consuming enzymes. To investigate the potential of such compounds to inhibit the adenosine diphosphate ribosyl (ADPr) transferase activity of the Legionella SdeC enzyme, we prepared three NAD + analogues, namely carbanicotinamide adenosine dinucleotide (c‐NAD + ), thionicotinamide adenosine dinucleotide (S‐NAD + ) and benzamide adenosine dinucleotide (BAD). We optimized the chemical synthesis of thionicotinamide riboside and for the first time used an enzymatic approach to convert all three ribosides into the corresponding NAD + mimics. We thus expanded the known scope of substrates for the NRK1/NMNAT1 enzyme combination by turning all three modified ribosides into NAD + analogues in a scalable manner. We then compared the three NAD + mimics side‐by‐side in a single assay for enzyme inhibition on Legionella effector enzyme SdeC. The class of SidE enzymes to which SdeC belongs was recently identified to be important in bacterial virulence, and we found SdeC to be inhibited by S‐NAD + and BAD with IC50 values of 28 and 39 μM, respectively. Abstract : Modestly modified : Three stable NAD + analogues namely, c‐NAD +, S‐NAD + and BAD were prepared by using an optimized chemoenzymatic procedure and were compared side‐by‐side for enzyme inhibition of Legionella effector enzyme SdeC, which is important in bacterial virulence. Minimal structural variation in the furanose ring or nicotinamide part of NAD + leads to efficient inhibitors.